"Activated Borane" - A Porous Borane Cluster Network as an Effective Adsorbent for Removing Organic Pollutants - Bůžek, Daniel; Škoch, Karel; Ondrušová, Soňa; Kloda, Matouš; Bavol, Dmytro; Mahun, Andrii; Kobera, Libor; Lang, Kamil; Londesborough, Michael G S; Demel, Jan (Chemistry (Weinheim an der Bergstrasse, Germany), 2022)
The unprecedented co-thermolysis of decaborane(14) (nido-B10 H14 ) and toluene results in a novel porous material (that we have named "activated borane") containing micropores between 1.0 and 1.5 nm in diameter and a specific surface area of 774 m2 g-1 (Ar, 87 K) that is thermally stable up to 1000 °C. Solid state 1 H, 11 B and 13 C MAS NMR, UV-vis and IR spectroscopies suggest an amorphous structure of borane clusters interconnected by toluene moieties in a ratio of about three toluene molecules for every borane cluster. In addition, the structure contains Lewis-acidic tri-coordinated boron sites giving it some unique properties. Activated borane displays high sorption capacity for pollutants such as sulfamethoxazole, tramadol, diclofenac and bisphenol A that exceed the capacity of commercially-available activated carbon. The consistency in properties for each batch made, and the ease of its synthesis, make activated borane a promising porous material worthy of broad attention.
Keywords: gas adsorption; activated borane; porous polymer; pollutant removal; decaborane